2022
DOI: 10.1007/s00259-022-05784-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of amyloid PET for future clinical use: a state-of-the-art review

Abstract: Amyloid-β (Aβ) pathology is one of the earliest detectable brain changes in Alzheimer’s disease (AD) pathogenesis. The overall load and spatial distribution of brain Aβ can be determined in vivo using positron emission tomography (PET), for which three fluorine-18 labelled radiotracers have been approved for clinical use. In clinical practice, trained readers will categorise scans as either Aβ positive or negative, based on visual inspection. Diagnostic decisions are often based on these reads and patient sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 214 publications
0
54
0
3
Order By: Relevance
“…This is also in line with the findings that showed that 26 Centiloids is an optimal cut-off in agreement with visual reads, which has been validated against CERAD pathology 23 , and with the 35.7 Centiloid cut-off for established Aβ abnormalities in PET described by Bullic et al 22 . Moreover, the range from 12 Centiloids to 30 Centiloids has been proposed to reflect the 'gray zone' of Aβ deposition 24 .…”
Section: Methodsmentioning
confidence: 99%
“…This is also in line with the findings that showed that 26 Centiloids is an optimal cut-off in agreement with visual reads, which has been validated against CERAD pathology 23 , and with the 35.7 Centiloid cut-off for established Aβ abnormalities in PET described by Bullic et al 22 . Moreover, the range from 12 Centiloids to 30 Centiloids has been proposed to reflect the 'gray zone' of Aβ deposition 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Our most recent focus is on the implementation of (Centiloid) quantification into the clinical routine, to not only support visual assessment of challenging cases, but also prepare the field for a potential necessity which could arise from the possible approval of disease-modifying therapies in the near future. To this end, academic and EFPIA partners collaborated on a comprehensive review regarding possible quantification approaches for the clinical setting ( 34 ) as well as engaging with regulatory bodies to share the in-depth knowledge that AMYPAD has gained using these methods during the course of the project. In this context, the AMYPAD team has investigated the robustness of the Centiloid quantification method ( 35 ), its feasibility in detecting early Aβ pathology ( 36 ), and its ability to detect changes over time.…”
Section: Pan-european Scientific Collaborationsmentioning
confidence: 99%
“…Several studies have reported that combining NLR metrics with positron emission tomography (PET)/computed tomography (CT) metabolic parameters can more clearly predict tumor survival time and biology [ 9 , 10 ]. PET is a pivotal molecular imaging tool for cancer diagnosis and imaging due to its relatively low spatial resolution and high sensitivity [ 11 ]. 18 F-fluorodeoxyglucose PET/CT ( 18 F-FDG PET/CT) can provide morphological and functional information for cancer management and is important for cancer diagnosis, staging, treatment planning, treatment response, and recurrence [ 12 ].…”
Section: Potential Tracers For Imaging Neutrophilsmentioning
confidence: 99%